The Self-Concept of Teenagers Who Hangout in Café: A Survey on Students - Natasha Stephana Chammearc; Fendra Firaldi Firdaus; Winda Rointan Tiurma Amelia Sianturi (Indonesian Journal of Multidisciplinary Science, 2023)
Café has become part of a lifestyle for most people. Café growing along with the development of modern places like Mall and Plaza. Hangout at the café is a trending lifestyle in the teenagers. This research use quantitative research approaches. This study aims is to provide an overview of self-concept of High School 53 Jakarta female students who conducting hanging out at cafe. The sample of this research was 120 female students of class XI High School 53 Jakarta. Purposive sampling technique was used as the sampling method. Survey method with questionnaires instrument was used to collect data for the research. The questionnaires consisted of 39 items which state about the teenagers confident. The results showed that 80% of female students who love to hang out at the café have a positive self concept. They could understand about themselves although there were a lot of external factors. They still conducted the social norms and could socialize well in home or school environment. As a positive sample, they used café as a place to eliminate the fatique they felt. They made use of the facilitates in the café to do positive activities such as did homeworks or did some research on budget.